2018
DOI: 10.1155/2018/3487591
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Regulatory Immune Response in Skin Lesions of Patients Affected by Nonulcerated or Atypical Cutaneous Leishmaniasis in Honduras, Central America

Abstract: In Honduras, Leishmania (L.) infantum chagasi causes both visceral leishmaniasis (LV) and nonulcerated or atypical cutaneous leishmaniasis (NUCL). NUCL is characterized by mononuclear inflammatory infiltration of the dermis, composed mainly of lymphocytes followed by macrophages with discrete parasitism. Considering that little is known about the pathogenesis of NUCL, the aim of this study was to evaluate the regulatory response in situ in skin lesions of patients affected by NUCL. Biopsies (n = 20) from human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 24 publications
1
22
2
9
Order By: Relevance
“…These lesions ulcerate, evolve over time and do not present a hypopigmented halo . These characteristics differ from the data presented in our study and by other authors regarding the disease observed in Central America where the lesions do not ulcerate regardless of the evolution time and are often surrounded by a hypopigmented halo . In both South America and Central America, patients do not have a previous history of VL.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These lesions ulcerate, evolve over time and do not present a hypopigmented halo . These characteristics differ from the data presented in our study and by other authors regarding the disease observed in Central America where the lesions do not ulcerate regardless of the evolution time and are often surrounded by a hypopigmented halo . In both South America and Central America, patients do not have a previous history of VL.…”
Section: Discussioncontrasting
confidence: 99%
“…However, we must take into account that little is known about human infection by Leishmania (L.) infantum chagasi in Honduras, especially cases involving the non‐ulcerated or atypical form. It should be noted that the only recently published study addressing the issue of NUCL in Honduras provides a brief histopathological description of the skin lesions caused by this parasite species . Thus, due to the scarcity of studies addressing this atypical clinical form of the disease, the objective of this study was to characterize in detail the histopathological changes of skin lesions in patients affected by NUCL and thus to better understand the pathogenesis of the infection caused by Leishmania (L.) infantum chagasi in Central America.…”
Section: Introductionmentioning
confidence: 99%
“…Another point that deserves to be highlighted regarding the ESI profile is its high frequency (25%) among the symptomatic infection profiles, being surpassed only by the frequency (30.8%) of the FSI profile, which denotes that, among the clinical-immunological profiles of symptomatic infection (NUCL), the ESI profile may also signal a state of adaptation of the parasite on the host skin, possibly seeking to produce an immune-inflammatory response of moderate intensity with the objective of using the host as a source of infection for the sand fly vector (Lutzomyia longipalpis). In this sense, there is already evidence obtained by our group pointing to the moderate presence of inflammatory response [13] as well as mediators of the immune-inflammatory response in the skin lesions of patients with NUCL [14].…”
Section: Discussionmentioning
confidence: 55%
“…Histopathological studies have shown that skin lesions of NUCL cases are characterized by a moderate mononuclear inflammatory infiltrate, predominantly formed by lymphocytes, with the presence of granulomas and scarce parasitism [ 13 , 14 ]. However, the co-occurrence of AVL and NUCL caused by L. (L.) infantum in the same geographic area suggests that host immunity factors may be involved in determining these different clinical forms of disease [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 Recently, the immunopathological features of the lesions from Honduran strains were microscopically described. 8 , 9 Alike most dermotropic Leishmania species, 10 , 11 the pro-inflammatory infiltrated in the dermis consisted of mononuclear cells including lymphocytes, macrophages and a few plasma cells. An interesting feature of the lesions was the scarcity of parasites even if the infiltrates were discreet or intense.…”
mentioning
confidence: 99%